THE RELATIONSHIP BETWEEN FERRITIN SERUM OF ANEMIA DURING PREGNANCY ON NEWBORN BIRTH WEIGHT - Citra Dewi Anitasari (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Anemia in pregnancy is a common health problem that occurs in the world, especially in development countries. Anemia during pregnancy due to deficiency of micronutrients such as iron, vitamin B12 and folic acid. The purpose of this study was to determine the relationship between serum ferritin of anemia during pregnancy on newborn birth weight. This is a cross sectional study. The population of study is all anemia during pregnancy who come to Lubuk Buaya Primary Health Care. The sample study that meets inclusion criteria amounting to 40 respondents taken with consecutive sampling technique. Examination of iron deficiency anemia during pregnancy on newborn birth weight was done in the Biomedical Laboratory of Andalas University by ELISA method. Statistical test using SPSS, Normality test with Shapiro-Wilk and Spearman test to see the relationship between iron deficiency anemia during pregnancy on newborn birth weight. The results showed that ferritin average level of anemia during pregnancy on newborn birth weight was 11,13 ± 6,37 with p> 0,05, r = 0,280. The conclusion of study is there is a possitive and not significant correlation between feerritin levels of anemia during pregnancy on newborn birth weight of anemia during pregnancy with newborn birth weight. It is recommended that pregnant women continue to consume Fe tablet during pregnancy and further research to see maternal obedience in consume Fe tablets.